Церковь Святой Великомученицы Екатерины конца XI в. в древнем Киеве - Красовский, И.С. (Археологія, 2006)
В статье рассмотрены реконструкция и месторасположение церкви Святой Великомученицы Екатерины конца ХI в. в Древнем Киеве. Проаналізувавши план Києва 1695 р., матеріали до рисунків руїн церкви А. Вестерфельда, автор дійшов висновку, що церкву Святої Великомучениці Катерини зведено в давньому Києві князем Всеволодом наприкінці XI ст. Having analyzed the plan of Kyiv of 1695 and the materials concerning a drawing of the ruins of the church by A. Vesterfeld, the author has come to a conclusion that the Church of Great Martyr Kateryna was built in ancient Kyiv by prince Vsevolod in late 11th c.